Application of the Singing Method in Learning English Vocabulary as an Effort to Increase Student Interest in Learning - Sunarti; Sujito (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2024)
Singing is a fun activity for children. Therefore, this method can be applied in learning English vocabulary, which is in fact a foreign language. Vocabulary learning is the first step for students to learn a language. At this stage of vocabulary learning, a fun method is needed to eliminate the notion that English is a language that is difficult to learn. The aim of this research is to find out to what extent the singing method for learning English vocabulary can increase students' interest or motivation to learn. The research used qualitative research methods using interviews and documentation in the data collection process and used data collection, data reduction, data presentation, and data verification in the data analysis process. The research results show that using the singing method in learning English vocabulary can increase students' enthusiasm for learning. This can be seen from the enjoyable learning process, and this situation has an impact on students' scores, which have increased, namely Melia Nazwa Putri's mid-semester scores was 75, her final semester scores was 85, as well as Muhammad Iqbal Ashari's mid-semester score was 80 to 85, and Jessica Safa Arbenita's mid-semester score was 80 to 83. In this way, students' scores increased from the scores obtained during the mid-semester assessment (PTS) and the scores obtained during the final semester assessment (PAS).